"Ghost" segregation pattern and ferroelectric domains in mixed calcium‐strontium‐barium niobates. (2nd July 2015) - Wierzchowski, W.; Wieteska, K.; Malinowska, A.; Wierzbicka, E.; Romaniec, M.; Lefeld‐Sosnowska, M.; Świrkowicz, M.; Łukasiewicz, T.; Sakowska, H.; Paulmann, C.; Paszkowicz, Wojciech; Kaszkur, Zbigniew; et al.
<x xml:space="preserve">Abstract</x> The defect structure investigations of selected ferroelectric niobates such as SrxBa1‐xNb2O6 (SBN), CaxBa1‐xNb2O6 (CBN) and mixed (Ca0.28Ba0.72)y(Sr0.61Ba0.39)1‐yNb2O6 (CSBN) single crystals grown by the Czochralski method have been performed by means of synchrotron and conventional diffraction topography and scanning electron microscopy. A new characteristic phenomenon has been indicated in CSBN crystals, which consisted in occurrence of two different systems of segregation fringes forming a crossing pattern. The first of them is the normal one, connected with the subsequent positions of the growth surface and coaxial with the core and the boundaries of the crystal. The second one, crossing the previous, is related to a kind of 'ghost' pattern reproducing some chemical composition changes in the new growing part of the crystal. Some rod‐like inclusions were also revealed around the core in the central part of samples cut out from various crystals. The scanning electron microscopic studies of selectively chemical etched samples revealed a domain structure in the SrxBa1‐xNb2O6, CaxBa1‐xNb2O6 and CSBN crystals. The ferroelectric domains were located along [001] direction. The domains, however, have not been revealed in the presented topographic experiments because of their small sizes. Copyright © 2015 John Wiley & Sons, Ltd.